Hydrophobic binding peptide-conjugated hybrid lipid-mesoporous silica nanoparticles for effective chemo-photothermal therapy of pancreatic cancer - Raj Kumar Thapa; Hanh Thuy Nguyen; Milan Gautam; Aarajana Shrestha; Eung Seok Lee; Sae Kwang Ku; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Taylor & Francis Group, 2017)
Nanoparticle-based drug delivery systems are designed to reach tumor sites based on their enhanced permeation and retention effects. However, a lack of interaction of these nanoparticles with cancer cells might lead to reduced uptake in the tumors, which might compromise the therapeutic efficacy of the system. Therefore, we developed bortezomib and IR-820-loaded hybrid-lipid mesoporous silica nanoparticles conjugated with the hydrophobic-binding peptide, cyclosporine A (CsA), and referred to them as CLMSN/BIR. Upon reaching the tumor site, CsA interacts hydrophobically with the cancer cell membranes to allow effective uptake of the nanoparticles. Nanoparticles ∼160 nm in size were prepared and the stability of IR-820 significantly improved. High cellular uptake of the nanoparticles was evident with pronounced apoptotic effects in PANC-1 and MIA PaCa-2 cells that were mediated by the chemotherapeutic effect of bortezomib and the photothermal and reactive oxygen species generation effects of IR-820. An in vivo biodistribution study indicated there was high accumulation in the tumor with an enhanced photothermal effect in PANC-1 xenograft mouse tumors. Furthermore, enhanced antitumor effects in PANC-1 xenograft tumors were observed with minimal toxicity induction in the organs of mice. Cumulatively, these results indicated the promising effects of CLMSN/BIR for effective chemo-phototherapy of pancreatic cancers.